Ideological Perspectives of Junior and Senior Academics on Factors Behind Yemeni Arabic-Speaking Student-Teachers’ English Deficiencies - Al-Hamzi, Ali Mohammed Saleh (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
Despite the strong emphasis that Non-Native English-speaking teachers place on English language proficiency, this study reveals that English language teachers graduating from public universities in an Arab country often lack essential communication skills due to gaps in their training. Using a Critical Discourse Analysis approach, this research draws on data from two sources to critically examine the inadequate English proficiency among student-teachers through an ideological lens. The findings highlight how differing ideological influences shaped various factors affecting the STs’ language competence. After all, these ideological forces have significant implications for the development of STs’ linguistic abilities.